RP-HPLC METHOD DEVELOPMENT AND VALIDATION FOR SIMULTANEOUS ESTIMATION OF OLMESARTAN MEDOXOMIL AND HYDROCHLOROTHIAZIDE - C.S. RITIHAAS; B.BHANU PRAKASH (International Journal of Pharma and Bio Sciences, 2015)
A Simple, Fast, Precise reverse phase isocratic high performance liquid chromatographic (HPLC) technique has been developed for the simultaneous estimation of Olmesartan medoxomil (OLM) and Hydrochlorothiazide (HCTZ) in marketed formulations. Estimation of these combined formulation was performed using Waters Symmetry C18 column (150 x 4.6 mm, 5µm) using the mobile phase of composition Methanol , Acetonitrile and Ammonium acetate buffer (50:25:25 v/v/v, pH 3.5). The flow rate was 1.0ml/min and the seperation was observed at 240nm. The retention time of OLM and HCTZ was found to be 3.34 min and 1.69 min respectively. The method was found to be linear over a range of 30 µg/ml for OLM and 18.75 µg/ml for HCTZ. The method was validated according to the guidelines of International Conference on Harmonisation (ICH) and was successfully employed in the estimation of commercial formulations.